Parallel esterification of bio‐based dicarboxylic acids in small scale film reactors: A high‐throughput study. Issue 8 (9th March 2021) - Hevus, Ivan; Webster, Dean C.; McNamara, John; Ricapito, Nicole G.; Tymoshenko, Stepan
Abstract: The applicability of polyesters across a wide range of fields creates a demand for novel polyester structures that can offer advanced product performance. Two critical factors to the development of unique polymer architectures are the speed at which new polymeric systems can be synthesized and the available selection of monomers from which polymers are designed. Herein, we successfully demonstrate the applicability of a high‐throughput (HT) approach to polyesterification reaction between dicarboxylic acids and diols in reaction conditions similar to those used in industry. Furthermore, we apply our HT design to a series of bio‐based monomers whose unique structures offer potential for enhanced properties in polyester‐based systems. Using a custom‐built array of small‐scale film reactors, we conducted a parallel screening of 13 bio‐based dicarboxylic acids as potential monomers in the synthesis of polyester polyols through copolymerization with 1, 6‐hexanediol. The polyester polyols were characterized for their molecular weight and thermal properties. Carrying out polyesterification reactions in small‐scale film reactors is seen as a quick and powerful tool for screening the effectiveness of a series of potential monomers, as this method offers highly controllable and reproducible reaction conditions in every reactor coupled with the ability to use a minimum amount of reagents. Abstract :